COMPETITIVE STRATEGIES CRITICAL SUCCESS FACTORS FOR SMALL MEDIUM FOOD AND BEVERAGES IN BOGOR CITY - Chandra Ayu Pramestidewi; Ismartaya (CV KULTURA DIGITAL MEDIA, 2022)
This observation is to determine the competitive strategy of small and medium food and beverage businesses in Bogor Municipality. The hope of this research is that by knowing the competitive strategy of small food and beverage businesses in the city of Bogor, the community will be able to improve and consider all elements of a competitive strategy. The sample of this research is entrepreneurs in the field of food and beverage small and medium enterprises in the city of Bogor. Sampling was done by simple random sampling, namely small and medium entrepreneurs in the food and beverage sector in the city of Bogor. Data obtained through primary data by distributing questionnaires, measured by Likert scale. Data analysis used descriptive analysis, regression analysis and t-test to test the hypothesis. The problem in this study is what factors influence the competitive strategy of small and medium food and beverage businesses in the city of Bogor, so it is necessary to analyze the critical success factors for competitive strategies, including: 1. Marketing (pemasaran), 2. Support (pendukung), 3. Organization (organisasi) of food and beverage SMEs in Bogor City. The purpose of this study is to determine the factors that influence the competitive strategy of food and beverage SMEs in the city of Bogor, it is also useful for the development of the next strategy with higher quality products and to be able to survive and compete in the business world.